Bond-slip modeling of a CMC rockbolt element using 2D-DDA method - Nie, Wen (2021)
The bonding condition at the rock and rockbolt interface is one of the most important factors to determine the load transfer mechanism of a CMC rockbolt element. The two-dimensional Discontinuous Deformation Analysis (2D-DDA) method is used in this paper to investigate the pullout performance of the CMC rockbolt element which is modeled as three components, i.e. the rock, the rockbolt and the mortar. The material properties used in the numerical models are calibrated against the experiments results. The simulated results show that a bond stress versus slip displacement curve of the CMC rockbolt element is exhibiting three stages which could be represented by a trilinear bond-slip model. Parametric studies have been carried out to investigate the effects of the confining pressure and those of the geometry configuration of the rockbolt ribs on the bond stress versus slip displacement curves and the crack propagations in the mortar. It is found that the maximum bond strength and the residual bond strength increase with the increase of confining pressure. Under lower confining pressure, the rib face angle controls the dilation of rock blocks. The obtained key parameters of the trilinear bond – slip models can be used to simulate the bond behavior between the rockbolt and rock interface in pullout test. The nodal axial forces and nodal bond force distributions along the rockbolt could be curve fitted using exponential models. The obtained parameters of the exponential models can be used for engineering practice under similar conditions.